PANEL INDICATORS OF INDUSTRIAL ACTIVITIES FOR WASTE: BALANCED SCORECARD OF WASTE MANAGEMENT (BSMW) - Jerônimo, Carlos Enrique de Medeiros; Fentanes, Luciana (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
This paper presents a proposal for a panel of indicators for assessing the performance of industrial solid waste management, called the Balanced Scorecard Management of Waste (BSMW). This element was based on 17 indicators that measure data on waste generation and collection, management of physical infrastructure support, treatment and disposal, cost management and treatment of accidental scenarios. The results were measured in a large organization of the petrochemical sector, and it was the end of one year of monitoring data results to a global index of quality of management, BSMW equal to three. What is an immaturity in the management of that enterprise, and an adherence to the policy elements of the organization's environmental management. The model was considered acceptable and is configured as a source for comparative studies between different branches or organizations.